2011
DOI: 10.1039/c1nr10399g
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting nanocomposite CdS–polymer electrospun fibres via in situ nanoparticle generation

Abstract: We report on the simple, in situ generation of CdS nanocrystals inside electrospun polymer fibres by thermal decomposition of a cadmium thiolate precursor, leading to nanocomposite light-emitting fibres. The modifications induced in the precursor by the thermal decomposition are investigated by a morphological, structural and spectroscopic analysis of the resulting nanocomposite fibres. This approach allows us to overcome nanofabrication difficulties related to disfavoured micro- or nanofluidic molecular flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…Rheological Characterization : Thermo‐analysis of the precursor decomposition showed that the complex started to decompose below 170 °C with a weight loss of ˜9% at 160 °C 43, 45. Rheological measurements were carried out by a rotational rheometer (TA Instruments Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheological Characterization : Thermo‐analysis of the precursor decomposition showed that the complex started to decompose below 170 °C with a weight loss of ˜9% at 160 °C 43, 45. Rheological measurements were carried out by a rotational rheometer (TA Instruments Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we report on light‐emitting patterned polymer–nanoparticle composites and fibers obtained by the smart combination of complementary nanofabrication approaches ( Figure ), aimed to exploit the most favorable flow conditions of nanocomposite materials. The synthesis is accomplished in one step , made possible by using a unimolecular precursor containing both the metal and non‐metal part of the semiconducting nanocrystals, and electron‐beam lithography (EBL) is used for the in situ synthesis of CdS nanocrystals in polymer matrices, after room‐temperature nanoimprinting lithography (RT‐NIL, Figure 1b)42 and electrospinning (Figure 1c),43 thus leading to various classes of composite nanostructures.…”
mentioning
confidence: 99%
“…In particular, the increase of the overall viscosity, the delayed thermomechanical response, and the control on the dispersion uniformity may strongly limit the possibility of shaping composites in the form of nanostructures or wires, which would benefit of an enhanced surface active area and additional possibilities of device design. In this respect, the implementation of low‐temperature methods for the in situ synthesis of BaTiO 3 NPs into a preformed polymer matrix, analogously to previous studies on light emissive nanocrystals, is especially interesting in view of realizing energy harvesting composites. Also, graphene and its derivatives have recently emerged as alternative fillers for PVDF .…”
Section: Polymer‐based Ngsmentioning
confidence: 99%
“…In this way, nanocomposite fibers are electrospun with absorption and emission in the visible and near infrared spectral range, by using inorganic NPs (i.e., metallic, such as Ag, Au, Pd and Pt, with size‐tunable absorption, or semiconducting from II–VI or III–V elements, with size‐tunable electronic band gap and emission bands) . Optically active nanocrystals are embedded in electrospun NFs by two methods: mixing ex situ colloidal particles with the organic solution, or synthesis in situ following the embedment of suitable molecular precursors in the fibers and decomposition by thermal treatment, optical or electron‐beam exposure, and gas reaction . The first method generally allows for more precisely controlling the size distribution of particles, and, consequently their optical bands .…”
Section: Optical Sensorsmentioning
confidence: 99%